Five New Pregnane Glycosides from Gymnema sylvestre and Their α-Glucosidase and α-Amylase Inhibitory Activities - Phan Van Kiem; Duong Thi Hai Yen; Nguyen Van Hung; Nguyen Xuan Nhiem; Bui Huu Tai; Do Thi Trang; Pham Hai Yen; Tran Minh Ngoc; Chau Van Minh; SeonJu Park; Jae Hyuk Lee; Sun Yeou Kim; et al. (Molecules, 2020)
Gymnema sylvestre, a medicinal plant, has been used in Indian ayurvedic traditional medicine for the treatment of diabetes. Phytochemical investigation of Gymnema sylvestre led to the isolation of five new pregnane glycosides, gymsylosides A–E (1–5) and four known oleanane saponins, 3β-O-β-D-glucopyranosyl (1→6)-β-D-glucopyranosyl oleanolic acid 28-O-β-D-glucopyranosyl ester (6), gymnemoside-W1 (7), 3β-O-β-D-xylopyranosyl-(1→6)-β-D- glucopyranosyl-(1→6)-β-D-glucopyranosyl oleanolic acid 28-O-β-D-glucopyranosyl ester (8), and alternoside XIX (9). Their structures were identified based on spectroscopic evidence and comparison with those reported in the literature. All compounds were evaluated for their α-glucosidase and α-amylase inhibitory activities. Compounds 2–4 showed significant α-amylase inhibitory activity, with IC50 values ranging from 113.0 to 176.2 µM.